Impact of packaging color on choice and health perception: Insights from chickpeas and ravioli in Germany - Saskia Buse; Stephan G.H. Meyerding (Journal of Agriculture and Food Research)
The global rise in obesity linked to poor nutrition behavior underscores the importance of promoting a healthy diet. This study investigates the impact of packaging color on consumer choice and health perception of chickpeas (a healthy product) versus ravioli (an unhealthy product) in Germany. Two choice experiments (CEs) were conducted with 222 participants aged 19 to 35, examining the influence of packaging color, label, price, and origin on product selection. Additionally, an image query assessed health perceptions associated with six different colored chickpea cans.The results indicate that price is the most influential factor in product choice for both chickpeas and ravioli, while packaging color has the least influence. However, green packaging significantly enhances health perception, with participants associating it with healthiness and environmental friendliness. In contrast, red packaging does not convey health value and is not linked to healthiness. Light blue packaging negatively affects health perception, partly due to associations with artificial additives. Beige packaging slightly improves health perception, while silver and black are perceived as indicators of quality but can also make the product appear less healthy.These findings highlight the complex role of packaging color in consumer behavior and suggest that while price remains a dominant factor, strategic use of color can enhance health perceptions and potentially influence healthier food choices. Future research should explore these effects across different cultural contexts and incorporate psychophysical methods to further understand the underlying mechanisms of color perception.